2007
DOI: 10.1186/1897-4287-5-3-161
|View full text |Cite
|
Sign up to set email alerts
|

Prostate screening uptake in Australian BRCA1 and BRCA2 carriers

Abstract: H He er re ed di it ta ar ry y C Ca an nc ce er r i in n C Cl li in ni ic ca al l P Pr ra ac ct ti ic ce e 2007; 5(3) A Ab bs st tr ra ac ct t Men who carry mutations in BRCA1 or BRCA2 are at increased risk for prostate cancer. However the efficacy of prostate screening in this setting is uncertain and limited data exists on the uptake of prostate screening by mutation carriers. This study prospectively evaluated uptake of prostate cancer screening in a multi-institutional cohort of mutation carriers. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, studies examining the impact of men at risk of prostate cancer and the associated recruitment and retention into early detection programs have shown that these programs are becoming more prevalent (10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies examining the impact of men at risk of prostate cancer and the associated recruitment and retention into early detection programs have shown that these programs are becoming more prevalent (10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In multiple large genomic cohort studies of primary PCa and metastatic castration-resistant prostate cancer (mCRPC), a number of DNA copy number variations (CNV), gene mutations, gene rearrangements, and gene fusions have been associated to disease recurrence [ 13 , 14 ]. Furthermore, familial mutations in transcription factors such as HOXB13 [ 15 ], tumor suppressor genes such as TP53 and APC [ 16 ], and DNA repair genes such as POLD1 , BRCA1 and BRCA2 [ 17 , 18 ], have also been discovered in PCa genomic studies.…”
Section: Single Omics In Pcamentioning
confidence: 99%